Status Ibu Bekerja dan Teman Sebaya terhadap Perkembangan Moral Anak : The Status of Working Mothers and Peers on Children's Moral Development - Sangadji, Hatifin; Ruswanti, Ruswanti; Purnama, Agus (MPI Press, 2023)
Introduction: The transformation of judgments of behavior, feelings, and reasoning into either right or wrong is referred to as moral development. There are three forms of moral classification, namely Preconventional, Conventional, and Postconventional. Objective: The research aims to analyze the moral development of children influenced by peer relationships and the mother's employment status. Method: The research adopts a cross-sectional approach in a quantitative research design. The population involved in the study consists of students in grades 5 and 6, with a sample size of 80 students. The sampling method used is total sampling. Data collection is done through a questionnaire, and data analysis employs the chi-square test. Results: Based on calculations using the chi-square method, the p-value for the variable of the mother's employment status is 0.024, while the p-value for the peer relationship variable is 0.514. Conclusion: The moral development of children is not influenced by peer relationships and the mother's employment status.